Media Capture: How Money, Digital Platforms, and Governments Control the News, Anya Schiffrin (ed.) (2021). Issue 1 (1st June 2022) - Tiffen, Rodney
Review of: Media Capture: How Money, Digital Platforms, and Governments Control the News, Anya Schiffrin (ed.) (2021)New York: Columbia University Press, 328 pp., ISBN 978-0-23118-882-1, h/bk, USD 120.00ISBN 978-0-23118-883-8, p/bk, USD 30.00ISBN 978-0-23154-802-1, e-book, USD 29.99